Anti-endothelial cell antibodies in connective tissue diseases associated with pulmonary arterial hypertension - Liu, Xiao-Dan; Guo, Sheng-Yu; Yang, Li-Li; Zhang, Xiao-Li; Fu, Wen-Yi; Wang, Xiao-Fei (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Objective: To investigate the prevalence of anti-endothelial cell antibodies (AECA) in connective tissue diseases (CTD) associated with pulmonary arterial hypertension (PAH) and to corroborate the pathologic function of AECA in PAH-associated CTDs. Methods: AECA were detected by cellular enzyme-linked immunosorbent assay (ELISA) in sera of 19 PAH-associated CTD patients, 22 CTD patients without PAH involvement, and 20 age- and sex-matched healthy individuals as controls. Using IgG purified from the sera of AECA-positive, AECA-negative, and healthy subjects, the effects of AECA on the expression of ICAM-1 and the chemokine regulated upon activation normal T-cell expressed and secreted (RANTES) in cultured endothelial cells were also evaluated. Results: A total of 12 of the 19 (63.2%) CTD patients with PAH, 9 of the 22 (40.9%) CTD patients without PAH, and 1 of the 20 (5%) healthy controls were positive for AECA, which were calculated as ELISA ratio (ER) values. ER values in PAH-associated CTD patients were significantly higher than those with CTD without PAH (3.68±2.05 versus 1.67±1.07, P